Side effects of steroid-sparing agents in patients with bullous pemphigoid and pemphigus: A systematic reviewCapsule Summary - Faith A.P. Zeng; Anna Wilson, MD, BMedRadSc; Tabrez Sheriff, MD; Dedee F. Murrell, MA, BMBCh, MD, FACD, DSc (Elsevier, 2022)
Background: Systemic glucocorticoids are first-line treatment options for autoimmune blistering diseases; however, their long-term use is associated with significant toxicities. Objective: To evaluate the side effects of steroid-sparing agents and compare them with those of steroids. Methods: We searched Cochrane Reviews, Embase, MEDLINE, and Scopus between October 1978 and May 2020 using the keywords "bullous pemphigoid," "pemphigus," "autoimmune blistering diseases," and "side effects." A total of 31 randomized controlled trials and retrospective case series were critically appraised. Results: This review includes a total of 1685 patients with autoimmune blistering diseases, of whom 781 had bullous pemphigoid and 904 had either pemphigus vulgaris or pemphigus foliaceous. Limitations: A major limitation is that because adjuvants are generally used in combination with steroids, only 12 of the studies reviewed included a "steroid-only" arm to allow for a direct comparison of side effects. Additionally, there is inadequate literature and lack of standardized grade reporting of specific side effects of each steroid-sparing agent. Conclusion: In the future, researchers should consider implementing the Common Terminology Criteria for Adverse Events, version 5.0, for reporting of all side effects to allow for consistency and standardization. It would be useful to have an index similar to the Glucocorticoid Toxicity Index to quantify these side effects.